School Well-Being and Self-Adjustment Among Vocational High School Students: Kesejahteraan Sekolah dan Kemampuan Beradaptasi Diri di Kalangan Siswa Sekolah Menengah Kejuruan - Wandana, Moch. Randy Nouval Putra; Nastiti, Dwi (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Students often struggle with forming harmonious relationships, breaking rules, and adjusting to school demands. Specific Background: School well-being is a key factor influencing students’ ability to adapt socially and emotionally in school. Gap: Few studies focus on vocational school students, despite their unique challenges. Aim: This study investigates the relationship between school well-being and self-adjustment among class 10 students at Krembung Islamic Vocational School. Method: A correlational quantitative design was used with 202 randomly selected students, employing school well-being and self-adjustment scales with high validity and reliability. Data were analyzed using Pearson Product Moment correlation. Results: Findings indicate a significant positive relationship (r = 0.662, p < 0.05), with school well-being contributing 43.5% to self-adjustment variance. Novelty: This research highlights the importance of school well-being in vocational education contexts. Implications: Schools should enhance physical, social, and psychological environments to improve students’ adjustment and participation.Highlight: Positive link between well-being and adjustment Contribution of school environment to behavior Practical recommendations for schools Keyword: School Well-Being, Self-Adjustment, Vocational School, Student Behavior, Correlation